Color M-Mode Echocardiography for Non-Invasive Assessment of the Intraventricular Pressure in Dogs Before and After Ductus Arteriosus Occlusion: A Retrospective Study - Hirose, Miki; Mandour, Ahmed S.; Goya, Seijirow; Hamabe, Lina; Matsuura, Katsuhiro; Yoshida, Tomohiko; Watanabe, Momoko; Shimada, Kazumi; Uemura, Akiko; Takahashi, Ken; Tanaka, Ryou (Frontiers in Veterinary Science, 2022)
Background Novel non-invasive evaluation of the intraventricular pressure differences and gradients (IVPD & IVPG) by color M-mode echocardiography (CMME) is a promising method in diastolic function evaluation. Patent ductus arteriosus (PDA) is a congenital heart defect with increased preload. The present work provides a clinical assessment of IVPD and IVPG changes in dogs before and after surgical treatment of PDA. Material and methods A total of 12 client-owned dogs were enrolled in this study. PDA was confirmed using echocardiography, and all dogs underwent PDA occlusion. Conventional echocardiography and CMME were conducted on each patient on the operation day (Pre-PDA) and 48 hours post-PDA occlusion. The IVPD- and IVPG-associated indices were measured from Euler’s equation using specific software (MATLAB). Data were analyzed for variability, the difference between Pre- and Post-PDA. The effect of PDA occlusion on evaluated variables was calculated using biserial ranked correlation (rc). Results There was a significant reduction in end-diastolic volume, fraction shortening, stroke volume, and mitral inflow velocities after PDA closure. CMME was feasible in all dogs and the CMME indices showed moderate variability except for the Apical IVPD and Apical IVPG. After PDA closure, in comparison with the Pre-PDA occlusion, there was a significant reduction in Total IVPD (2.285 ± 0.374 vs 1.748 ± 0.436 mmHg; p=0.014), Basal IVPD (1.177 ± 0.538 vs 0.696 ± 0.144 mmHg; p= 0.012), Total IVPG (1.141 ± 0.246 vs 0.933 ± 0.208 mmHg; p= 0.032), and Basal IVPG (0.578 ± 0.199 vs 0.377 ± 0.113 mmHg; p= 0.001); meanwhile, Mid, Mid-to-apical, and Apical segments of both IVPD and IVPG showed non-significant difference. The magnitude of PDA occlusion on measured variables was clinically relevant and associated with a large effect size on Total IVPG and Basal IVPG (rc range: 0.692 ̶ 1.0). Conclusion The current clinical study revealed matched response of IVPD and IVPG to the reduced preload rather than LV relaxation. This result is an initial step into the clinical utility of CMME-derived IVPD and IVPG assessment in diastolic function evaluation that warrants further clinical studies.